Corporate social responsibility and purchase intentions: perceptions and expectations of young consumers' in Ghana. (28th August 2019) - Neequaye, Emmanuel Kotey; Amoako, George Kofi; Attatsitsey, Mayqueen
Despite the growing practice of corporate social responsibility (CSR) within the telecommunications industry of Ghana, it has received limited research attention. Thus, the primary purpose of this study is to examine perceptions and expectations of consumers' regarding Airtel Ghana CSR initiatives, consider their impact on purchase intentions and identify any gap between consumers' perceptions and their expectations of Airtel Ghana CSR initiatives. A cross-sectional survey was adopted for this study and the study is quantitative in nature. The results suggest philanthropic and legal CSR were the current main drivers of Airtel Ghana consumers' purchase intentions. However, based on their expectations, Airtel Ghana consumers' wished their purchase intensions were driven by economic and ethical CSR practices instead. The researchers' discuss managerial and theoretical implications of the research results. Future research will adopt the three part model of CSR and findings compared to get a view of CSR from different perspectives.